東京湾奥部におけるイッカククモガニPyromaia tuberculataの個体群構造 - 風呂田, 利夫 (日本ベントス学会誌, 1990)
Monthly samples of the introduced spider crab have been taken over three years in the innermost area of Tokyo Bay. Adult spider crabs were killed by oxygen deficiency in late summer, and recruitment occurred in late fall. Young crabs grew through winter, and reached maturity by early spring ; females began carrying eggs soon after maturation. From spring to early summer, the crab population consisted principally of matured males and females (>9 mm in carapace width) ; larvae were produced throughout this period. Young crabs (<5 mm in carapace width) produced in these seasons were found during late spring to early summer ; most, however, disappered before maturing along with adults when the summer oxygen deficiency was established. Seasonal changes in the population structure showed almost the same pattern in three years. This indicates that larvae produced in the innermost region of the bay do not contribute to the recruitment, and that the crab population in this region is maintained by settlement of larvae during late fall which may be produced from individuals surviving in the oxygen rich environment in mixed region of the bay.